The effect of virtual reality simulation on nursing students’ communication skills: a systematic review and meta-analysis - Cho, Mi-Kyoung; Kim, Mi Young (Frontiers in Psychiatry, 2024)
﻿Virtual reality simulation (VRS) allows individuals to experience a sense of presence in a virtual environment, and it has been increasingly adopted as a novel teaching method in nursing education. VRS can have positive effects, such as patient safety, privacy assurance in healthcare, and enhanced interest and immersion in education. It is important to synthesize the results to date to determine if VRS has the potential to improve communication skills in practical nursing students. This systematic literature review and meta-analysis investigated the effect of VRS on the enhancement of communication skills among nursing students. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were employed for systematic review and meta-analysis. The following “PICO” details were considered: population—nursing students, intervention—VRS targeting communication skills enhancement, comparator—control groups without intervention or those undergoing general classes, and outcomes—communication skills. The search strategy yielded 301 results from nine databases, and 10 studies were selected for inclusion in our analysis. To calculate the overall effect sizes of the primary and secondary outcomes in the included studies, we used MIX 2.0 Pro (Version 2.0.1.6, BiostatXL, 2017) for the meta-analysis. The overall effect size for communication skills was 0.44, signifying a significant effect. A meta-regression analysis examining communication skills revealed significant results for the following factors: Fund (Ref.: No), outcome measurement time (Ref.: Immediately), outcome follow-up (Ref.: No), and debriefing (Ref.: No). Considering factors such as variations in sample size, research approaches, and the effects of independent studies on communication skills, this systematic literature review and meta-analysis suggests that VRS significantly improves nursing students’ communication skills overall.